1998
DOI: 10.1073/pnas.95.14.7882
|View full text |Cite
|
Sign up to set email alerts
|

Control of interferon-τ gene expression by Ets-2

Abstract: Expression of the multiple interferon-(IFN-) genes is restricted to embryonic trophectoderm of ruminant ungulate species for a few days in early pregnancy. The promoter regions of these genes are highly conserved. A proximal (bp ؊91 to ؊69) sequence has been implicated in controlling trophoblast-specific expression. Here it was used as a target for yeast one-hybrid screening of a day 13 conceptus cDNA library. Two transcription factors of the Ets family, Ets-2 and GABP␣, were identified, consistent with the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 48 publications
3
112
0
2
Order By: Relevance
“…Transfection experiments confirmed that the proximal-most site, is essential for gene expression. When part of this region was used as a target for yeast one-hybrid screening of a Day 13 conceptus library, the nuclear protein, Ets-2, was identified as binding to this site and to activate transcription (22). This element is adjacent to a putative AP1 site and two helical turns upstream of a binding site for the homeobox protein Dlx3.…”
Section: Transcriptional Control Of Ifnt Expressionmentioning
confidence: 99%
“…Transfection experiments confirmed that the proximal-most site, is essential for gene expression. When part of this region was used as a target for yeast one-hybrid screening of a Day 13 conceptus library, the nuclear protein, Ets-2, was identified as binding to this site and to activate transcription (22). This element is adjacent to a putative AP1 site and two helical turns upstream of a binding site for the homeobox protein Dlx3.…”
Section: Transcriptional Control Of Ifnt Expressionmentioning
confidence: 99%
“…Threonine 72-In a variety of cell types Ets-2 is regulated by the Ras-dependent MAPK ERK (10,11). Activated ERK phosphorylates Ets-2 at threonine 72, which results in transcriptional transactivation.…”
Section: Ras-mediated Activation Of Ets-2 In T-cells Is Dependent Onmentioning
confidence: 99%
“…Oncogenic (constitutively active) Ras in conjunction with Ets-2 super-activates promoters containing Ets-binding sites (10,11). Ras pathwaymediated activation of Ets-2 occurs through a conserved MAPK-docking motif, PLLTP, contained within amino acids 69 -73 of the Ets-2 protein.…”
mentioning
confidence: 99%
“…Presumably, Ets factors can play an important role in the activation of the PAG genes. The involvement of Ets factors in the control of IFN-τ has been shown in ruminants [30,31] or in specific control of human gene expression [32]. The activation of the PAG genes may also be controlled by other mechanisms or transcription factors that are indicated for cathepsin D promoter [33] or other placental promoters of hCG [34], Prl [35], Prl-like placental proteins [36,37] and lactogens [38].…”
Section: Exon-intron Structure Of the Pag Genes Promoters And Gene Nmentioning
confidence: 99%